Cost-Benefit Assessment of Climate-Restricted Airspaces as an Interim Climate Mitigation Option - Niklaß, Malte; Lührs, Benjamin; Dahlmann, Katrin; Froemming, Christine; Grewe, Volker; Gollnick, Volker (Journal of Air Transportation, 2017)
Within this study, climate-restricted airspaces are defined in analogy to military exclusion zones. Airspaces are closed if the climate sensitivity of an area exceeds a threshold value, and affected flight trajectories are rerouted cost optimally around them. The evaluation of the concept is performed based on optimal control techniques. Therefore, monetary costs and climate change functions (characterizing the environmental impact caused by an aircraft emission at a certain location and time) are integrated into the objective function of an aircraft trajectory optimization framework. The optimization of nine North Atlantic routes with monthly varying climate change functions indicates a potential for reducing the climate impact within the same order of magnitude as climate-optimized trajectories. A cost increase of only 1%may lead to reductions in climate impact of 10%. A highly seasonal dependency of the mitigation efficiency is found, and summer months offer the greatest potential for climate impact reduction. However, particularly small climate gradients in winter trigger huge zones of restrictions and might cause additional warming if the increase of fuel consumption for avoidance dominates the climate sensitivity reduction. Because the restriction of airspace areas might also affect airspace capacity adversely, this paper presents a market-based approach to overcome these issues.